1988
DOI: 10.1115/1.3125833
|View full text |Cite
|
Sign up to set email alerts
|

The Interface Crack Under Combined Loading

Abstract: The interface crack subjected to a combined tension-compression and shear loading is considered in the Comninou formulation, which by properly incorporating contact zones at the crack tips avoids contradictions, such as overlapping of material. It is shown that the resulting integral equation can be solved exactly. Moreover, simple asymptotic — yet very accurate — formulae are derived for the quantities of major physical interest and a comparison made with the previous results given by Comninou.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
78
1
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 0 publications
4
78
1
1
Order By: Relevance
“…Numerical difficulties were encountered when one of the contact zones was exceedingly small. The problem of an interface crack under combined loading was reconsidered in Reference [16] and the integral equation was solved accurately over the entire range of elastic constant mismatch. The same problem was addressed again in Reference [17]; it was shown that the normal gap and tangential shift satisfy an eigenvalue problem consisting of a second order ordinary differential equation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical difficulties were encountered when one of the contact zones was exceedingly small. The problem of an interface crack under combined loading was reconsidered in Reference [16] and the integral equation was solved accurately over the entire range of elastic constant mismatch. The same problem was addressed again in Reference [17]; it was shown that the normal gap and tangential shift satisfy an eigenvalue problem consisting of a second order ordinary differential equation.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of an interface crack under combined loading was reconsidered in Reference [16] and the integral equation was solved accurately over the entire range of elastic constant mismatch. The same problem was addressed again in Reference [17]; it was shown that the normal gap and tangential shift satisfy an eigenvalue problem consisting of a second order ordinary differential equation. The same technique, with the assumption of a monotonically increasing load, was used to address frictional contact of a crack subjected to pure bending [18] and the frictional contact problem of an interface crack in a shear field [19].…”
Section: Introductionmentioning
confidence: 99%
“…Comninou's work [6][7][8] is therefore usually called the contact model. Based on the contact model [6][7][8], Gautesen and Dundurs [9,10] and Gautesen [11] developed analytical theories for calculating physical quantities such as the contact zone size and the interface tractions.…”
Section: Introductionmentioning
confidence: 99%
“…When the surfaces near an interfacial crack tip are in contact, the conditions around the tip locally become pure mode II, at least before the crack kinks [Comninou 1977;Comninou and Dundurs 1979a;1979b;Fan et al 1998;Gautesen and Dundurs 1988]. Equivalently, the effect of contact can be included by applying a pure shear loading at infinity or by setting the loading phase angle to 90 • [Leblond and Frelat 2001;.…”
Section: Introductionmentioning
confidence: 99%